Reflective Practice: A Gateway to Professional Development - Pandey, Shiva Ram (Journal of NELTA, 2013)
The main purpose of this research paper is to explore the power of reflection in the teaching and learning process. The prime research question is how do English language teachers reflect their opinion and experience in reflective practice? This research is a qualitative study of English teachers from the Kathmandu district higher secondary schools. The results of this study show that reflective practice enhances teaching skills and brings changes in instructional practices. Teachers have to think, act and reflect tenaciously. As a result, the instructional process is activated and improved. It further presents that every incident has enormous insights to learn through this practice. Reflective practice enhances the professional development of English language teachers. Journal of NELTA, Vol. 17 No. 1-2, December 2012, Page 40-49 DOI: http://dx.doi.org/10.3126/nelta.v17i1-2.8091